A novel duplex droplet digital PCR assay for simultaneous authentication and quantification of Panax notoginseng and its adulterants. (February 2022) - Yu, Ning; Xing, Ranran; Wang, Ping; Deng, Tingting; Zhang, Jiukai; Zhao, Guiming; Chen, Ying
Abstract: Food adulteration can result in unfair commercial trade and consumer distrust, therefore, a reliable and effective method for food qualitative and quantitative analysis is necessary. In the present work, we developed a highly sensitive and precise approach based on duplex droplet digital PCR (ddPCR) for the identification and quantification of Panax notoginseng ( P. notoginseng ) powder and its adulterants. The detection targeted single copy nuclear genes, the limits of detection (LODs) for rice and soybean were both 0.1%, and the limits of quantifications (LOQs) were both 0.5%. The relationship between species proportions and DNA copy number was established for rice, soybean and P. notoginseng and the regression equation all exhibited good linearity. To further demonstrate the accuracy of the developed method, samples with known concentrations were tested. In general, the developed duplex ddPCR assays is useful for addressing adulteration issues in health food material powder from P. notoginseng . Highlights: DdPCR is used for quantification of health food powder and the adulterants. Duplex ddPCR can simultaneously and accurately quantify target products. The developed method targets single-copy nuclear gene for quantitative analysis.